Adoption, unwed mothers and the powers of the Children’s Aid Society in Ontario, 1921-1969 - Chambers, Lori (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
Canadian historians have not explored the means by which babies were acquired for adoption placement. The majority of children relinquished for adoption have historically been born to unwed mothers. How did the law frame the unwed mother’s relationship with the state and to her child? To what degree did the unwed mother exercise free and unfettered choice in relinquishing an infant for adoption? This article explores these questions. It is argued that the law denied unwed mothers choice; in a context of financial constraints at the CAS, ideological commitment to the adoption mandate, and a demand for (healthy white) babies, unwed mothers were subjected to coercive pressure to relinquish their babies. This article uses 563 adoption case files to illustrate these themes.